"On their own": social isolation, loneliness and chronic musculoskeletal pain in older adults. (12th June 2017) - Smith, Toby
Abstract : Purpose: The purpose of this paper is to explore the concepts of social isolation and loneliness in relation to people with chronic musculoskeletal pain. Through these concepts, biological, psychological and social factors will be examined to consider how we can identify people at risk of social isolation and loneliness who have chronic musculoskeletal pain and then how health professionals may intervene to reduce their effects. Design/methodology/approach: Conceptual paper. Findings: Social isolation and loneliness are often evident in the situation of people with chronic musculoskeletal diseases. This may be bi-directional where pains may lead to social isolation and loneliness, but equally, social isolation and loneliness may exacerbate pain. Interventions to improve the symptoms of chronic musculoskeletal pain, and also approaches around social participation and engagement should be adopted in combination to ameliorate this potentially disabling scenario. Originality/value: There remains limited evidence around the prevalence and management of social isolation and loneliness for people with chronic musculoskeletal pain. By raising awareness of social isolation and loneliness in this population, people with chronic musculoskeletal pain may be better supported to reduce the negative impact that social isolation and loneliness can have on their health and well-being.